Meriones Persicus as a New Probable Reservoir for Visceral Leishmaniosis - SSR Shojaei; M Mohebali (Tehran University of Medical Sciences, 2005)
Visceral leishmaniosis as a zoonotic disease is one of the important infectious disease due to severe side effects and mortality in children and because of at least two endemic foci in Iran (Firooz Abad and Djahrom in Fars State, Meshkin Shar and Moghan in Ardabil State). Despite all preventive procedures, the incidence of the disease has commonly increased which indicates the possible existence of other vertebrate's reservoirs in addition to carnivoirs (main reservoirs of the Mediterranean visceral Leishmaniasis); therefore, rodents were examined during this research (1995-1997) in the endemic region of Meshkin Shahr. Comprehensive parasitological studies were conducted. Serological tests (Direct Agglutination Test) and cultivation protozoa were done in 120 sample rodents, which were captured alive. The prepared blood smears were undergone microscopic studies. Rodents that showed positive titers in DAT were also undergone necropsy .The prepared impression smears from Reticulo endothelial tissues (Liver and Spleen) were cultivated in NNN media. The observed livers and spleens of many rodents showed very low titers in many cases but showed significant pathological signs (Hepatomegally and splenomegally) even compared to higher titer rodents. The research procedure was changed by just considering the pathological signs of livers and spleens of sample rodents and ignoring the results of DAT .All the suspicious organs were cultivated in NNN. The captured rodents were Meriones persicus (116), Mus musculus (3) Cricetulus migratorius (1) and for the first time in Iran Leishmania donovani was isolated from M.persicus. In isoenzyme studies, zymodeme of isolated L.donvani , LON 50, was identified. Among 116 M.persicus 10.3% showed positive parasitological results and 52.6% had sero titers between 1:10 to 1:200 in DAT.